Analisis Pengaruh Budaya, Kelompok Sosial, Pribadi Dan Psikologis Terhadap Keputusan Pembelian Laptop Merk Asus (Studi Kasus Toko Multika Komputer Di Kota Pasuruan) - M. Sulaiman; Rois Arifin; M. Hufron (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThis study aims to determine the effect of the influence of consumer behavior on purchasing decisions for ASUS brand laptops. The population and samples are all consumers of the Multika Computer store in the City of Pasuruan 2019 who use Asus Brand Laptops. The consumers at the Multika Komputer store and the research population are 275.In this study, using data analysis techniques such as questionnaires and interviews. The data analysis tool used in the study used an application in the form of software in the form of SPSS version 16. The method of research analysis was validity test, reliability test, normality test, multicolonierity test, heteroscedasticity test, multiple linear regression analysis, T test, F test. Partially that consumer behavior (culture, social group, personal, and psychological) has a significant effect on purchasing decisions and simultaneously that consumer behavior (culture, social group, personal, and psychological) has a significant effect on purchasing decisions. Keywords: Culture, Social Group, Personal, Psychological and Purchase Decisions.